Assessing the Change of Agroclimatic Suitability for Rice Cultivation in South Sumatra, Indonesia - Wandayantolis Wandayantolis; Dedik Budianta; Yakup Yakup; Dodo Gunawan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
This study examines variations in agro-climatic conditions for rice farming in South Sumatra, Indonesia, over four different periods: 1981-1990, 1991-2000, 2001-2010 and 2011-2020. The Oldeman classification was used by the research on rainfall-based satellite observation datasets to analyze agroclimatic zonation within the region. It was established that the B1 zone suitable for rice cultivation remained the dominant agro-climatic zone throughout all these years (50.7% to 62.7% of the total area). However, C2 zone had a massive increase from 0.4 percent between 1981 and 1990 to a significant level of up to 18.6 percent by the year ending in 2011–2020. However, Musi Banyuasin had an increase followed by decreasing precipitation, but not Empat Lawang, where there was a decline. From these results, it can be concluded that there are changing precipitation patterns concomitant with shifts in agroclimatic situations across each locality.